Effect of Business Performance on Taxation of Small and Medium Enterpries Scale in Bwari Area Council FCT Abuja, Nigeria - Israel O. E. Idewele (Budapest International Research and Critics University, 2020)
Tax remains a veritable means of developing a modern day economy and apart from the major sources of taxes such as Company Income Tax, Value Added Tax and Withholding-Tax. Apart from these taxes there is also taxation of the informal sector such as the SMEs. This study investigated the effects of business performance on taxation of Small and Medium Enterprise scale (SMEs) in Bwari Area Council FCT, Abuja. The study had a population of 156 and a sample size of 112 which was arrived at using Yamane sampling model. Data was gathered using questionnaires administered to the respondents and was analyzed using multiple regression technique. The findings revealed that return on assets and staff recruitment had positive and significant effect on taxation of SMEs in Bwari Area Council of FCT, Abuja. It was recommended amongst others that SMEs should engage in cost saving measures to boost their profits which encourage payment of taxes. It was also recommended that SMEs should employ optimally, their required numbers of staff to boost payment of taxation to Bwari Area Council FCT, Abuja